Effects of moisture on historical buildings TL ages. (March 2018) - Gueli, A.M.; Garro, V.; Liuzzo, M.; Margani, G.; Pasquale, S.; Politi, G.; Stella, G.
Abstract: This contribution is part of a multidisciplinary study on the Indirizzo Thermal Baths in Catania aimed to deepen the historical and architectural knowledge and the chronological framework. The application of ThermoLuminescence (TL) dating on the samples collected from the site, aimed to establish the chronology of the fabric, offers a starting point for a discriminating evaluation about the moisture effect on the age results. The water content is one of the most important values needed for age estimation and it must be taken into account for the dose rate calculation. The main goal of the present study is putting in evidence the importance of the wetness in the age calculation. To this purpose, some brick samples collected at specific points of the Indirizzo thermal baths were analysed assuming different water content values. The influence on age results was then discussed.